Quality changes kinetic of tomato during transportation and storage. (14th July 2021) - Al‐Dairi, Mai; Pathare, Pankaj B.; Al‐Yahyai, Rashid
Abstract: Kinetic models were performed to investigate the quality changes of tomatoes. The samples were transported from three different distances (100, 154, and 205 km), and then stored at a temperature of 10 and 22°C. Physical (weight loss, color, and firmness), chemical (titratable acidity (TA), total soluble solids (TSSs), sugar/acid ratio, and pH), and nutritional (total lycopene and carotenoids) quality parameters of tomato were measured for 12 days of storage. Transportation of tomatoes from the long‐distance transportation and storage at 22°C resulted in a higher increase in weight loss, redness, color index, total lycopene, and carotenoids, and a higher decrease in firmness, color lightness, TA, and so forth. The results showed that the quality changes were well described by the zero‐order kinetic model (with a coefficient of determination R 2  = values of .9993–.8400). Weight loss, total lycopene, and carotenoids were adequately fitted with the zero‐order kinetic model, where TSSs and most firmness experimental values were successfully fitted with the first‐order kinetic model. In all cases, the reaction rate constant ( k ) was higher at 22°C storage temperature compared to storage at 10°C. To validate the appropriateness of the selected models, weight loss, firmness, some color parameters, TA, and total lycopene were taken as examples. All the experimental and predicted data showed a strong agreement. Overall, the results of this study could help the distributors, processors, and consumers to identify the storage time and the ideal edible time. Practical applications: The practical application obtainable from our research is the classification of fresh produce based on their maturity stage is required to select the suitable packaging with high strength material during long‐distance transportation. Also, the practical objective of the study is to improve refrigeration storage condition of tomato or many other fresh produce after transportation in the industrial field to maintain its quality attributes for long time. In particular, the proposed study establishes the correlation between transport distance, storage temperature, and duration and the quality attributes of tomato to obtain a mathematical model to predict the quality changes during storage and to assess the effect of transport distance on tomato. The knowledge of such type of data can help to develop an advanced supply chain strategies like transporting, storage, and routing policies. Abstract :